GP decisions to participate in emergencies: a randomised vignette study - Hjortdahl, Magnus (BJGP Open, 2021)
BACKGROUND: GPs use their judgement on whether to participate in emergencies; however, little is known about how GPs make their decisions on emergency participation. AIM: To test whether GPs' participation in emergencies is associated with cause of symptoms, distance to the patient, other patients waiting, and out-of-hours (OOH) clinic characteristics. DESIGN & SETTING: An online survey was sent to all GPs in Norway (n = 4701). METHOD: GPs were randomised to vignettes describing a patient with acute shortness of breath and asked whether they would participate in a callout. The vignettes varied with respect to cause of symptoms (trauma versus illness), distance to the patient (15 minutes versus 45 minutes), and other patients waiting at the OOH clinic (crowding versus no crowding). The survey included questions about OOH clinic characteristics. RESULTS: Of the 1013 GPs (22%) who responded, 76% reported that they would participate. The proportion was higher in trauma (83% versus 69%, χ(2) 24.8, P<0.001), short distances (80% versus 71%, χ(2) 9.5, P=0.002), and no crowding (81% versus 70% χ(2) 14.6, P<0.001). Participation was associated with availability of a manned-response vehicle (adjusted odds ratio [OR] 2.06, 95% confidence interval [CI] = 1.25 to 3.41), and team training at the OOH clinic once a year (OR = 1.78, 95% CI = 1.12 to 2.82) or more than once a year (OR = 3.78, 95% CI = 1.64 to 8.68). CONCLUSION: GPs were less likely to participate in emergencies when the incident was not owing to trauma, was far away, and when other patients were waiting. A manned-response vehicle and regular team training were associated with increased participation.